National innovation capacity and economic progress of countries - Slobodan Cvetanović; Andrea Andrejević Panić; Aleksandar Kostić (Economic Themes, 2021)
The ability of the national economy to create and to valorize innovations on the market in order to produce economic goods represents its national innovation capacity, which is at the same time a key determinant of countries' economic progress. Due to this fact, its relevance imposes the task of identifying, as accurately as possible, the key theoretical postulates on which this concept is based, as well as calculating the Innovation capacity index by which it is possible to predict progress in building innovation capacity of individual countries and mutual comparison with other countries according to innovation capabilities. After a brief explanation of the essence of learning, on which this concept is based, an attempt is made to calculate the Innovation capacity of the European Union and the Western Balkans, on the one hand, and to consider the interdependence of the obtained results and the achieved level of their economic development in 2020, on the other hand. The results of the research confirmed the strong connection between the Innovation capacity index and the achieved level of economic development of countries expressed in terms of gross domestic product per capita.
Keywords: O3; 330; national innovation capacity; national innovation system; Innovation capacity index; knowledge; innovation; EU; The Western Balkans